A parallel and silent emerging pandemic: Antimicrobial resistance (AMR) amid COVID-19 pandemic - Suriya Rehman (Journal of Infection and Public Health, 2023)
World is in the middle of the pandemic (COVID-19), caused by SARS-COV-2 virus, which is a significant global health crisis after Spanish influenza in the beginning of 20th century. Progressive drastic steps have been enforced to minimize the transmission of the disease. Likewise, in the current years, antimicrobial resistance (AMR) has been referred as one of the potential perils to the global economy and health; however, it is now veiled under the present pandemic. During the current pandemic, AMR to available frontline antibiotics may prove fatal and life threatening to bacterial and fungal infections during routine procedures like elective surgery, C-sections, etc. Currently, a swift elevation in multidrug-resistant organisms (MDROs), like carbapenem-resistant New Delhi metallo-β-lactamase (NDM)-producing Acinetobacter baumannii, Enterobacterales, extended-spectrum β-lactamase (ESBL)-producing Klebsiella pneumoniae, methicillin-resistant Staphylococcus aureus (MRSA), multi-triazole-resistant Aspergillus fumigatus and pan-echinocandin-resistant Candida glabrata has been seen. Thereupon, the global outbreak of COVID-19 also offers some important ramification for developing antimicrobial drug resistance. This article aims to highlights episodes and aspects of AMR prevalence, impact of management and mismanagement of COVID-19 crisis, hospital settings, community, environment, and travel on the AMR during the current pandemic.